Test Case Generation Using Visual Contracts - Runge, Olga; Khan, Tamim; Heckel, Reiko (Electronic Communications of the EASST, 2013)
Visual contracts provide a diagrammatic notation for pre- and postconditionsas alternative to the Object-Constraint Language (OCL) or code-levelcontract languages. Using visual contracts for testing, we benefit from their executabilityand formal background in graph transformation to provide model-basedtest oracles and coverage criteria. Based on a static analysis of their dependenciesand conflicts, in this paper we use visual contracts to generate test cases accordingto these coverage criteria.Together with previous work, this adds up to a comprehensive approach aiming toautomate the three major challenges of testing through the use of models.